British Women’s Roles during the Second World War 1939-1945 - Benzaama, Sara Lelloucha (My University, 2017)
The aim of the present paper is to investigate and identify the roles of British Women during the Second World War 1939_1945. The thesis details the ways in which Women were experienced a variety of roles from country to another, how they were treated in the domestic service, the workforce and the armed forces as the best example of the successful mobilization of the energies and abilities of Women in the service of nation. In the Second World War, Women were more active in the military through auxiliary groups such as Women’s Auxiliary Air Force and it is important to understand how much of an impact their work made on the Allies war effort. The present paper concludes that British Women played a major role during World War Two, however at the end they found that the advances they had made were greatly reduced and the attitudes to the role of Women in the services were changed forever.
Keywords: Great Britain; Role and rise of women; World war two 1939-1945